Functional Surgical Resection in Glioma Patients: A Literature Review on Techniques and Outcomes - Barus, Brian Jovi; Sebayang, Moriko Madadoni; Ginting, Muhammad Rafif (Talenta Universitas Sumatera Utara, 2025)
Background: Gliomas frequently invade eloquent cortical and subcortical regions, necessitating surgical strategies that optimize oncological resection while preserving neurological integrity. Functional surgical resection integrates advanced modalities to achieve maximal safe resection. Method: A structured qualitative literature review was performed, synthesizing current evidence from high-impact databases on intraoperative techniques including awake craniotomy, cortical and subcortical mapping, fluorescence-guided resection, and intraoperative imaging and their impact on surgical outcomes in glioma patients. Discussion: Functional mapping and imaging adjuncts significantly improve the extent of resection and mitigate postoperative deficits, particularly in IDH-mutant low-grade gliomas and eloquent high-grade lesions. However, limitations in fluorescence efficacy, imaging resolution, and resource availability persist across institutions. Conclusion: Functional resection techniques enhance survival and quality of life by enabling individualized, anatomically precise glioma surgery. Future directions include integration of molecular diagnostics, intraoperative tools, and global standardization to reduce outcome disparities. Keyword: Glioma, Functional Surgical Resection, Awake Craniotomy, Cortical Mapping, Neuronavigation, Electrophysiological Monitoring